Effectiveness of acupuncture for post-stroke aphasia: protocol for a systematic review and meta-analysis - Junzhe Jia; Yuanli Shan; Yihe Tang; Qiang Tang (Frontiers in Neurology, 2025)
BackgroundPost-stroke aphasia (PSA) is a prevalent and debilitating consequence of stroke, significantly impairing communication abilities and reducing patients’ quality of life. While speech and language therapy represents standard care, many patients experience incomplete recovery. Acupuncture, a key component of traditional Chinese medicine, offers a potential complementary approach for enhancing language rehabilitation. This protocol describes a planned systematic review and meta-analysis to synthesize evidence on the effectiveness and safety of acupuncture for patients suffering from post-stroke aphasia.Methods and analysisWe will systematically search PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure (CNKI), Wanfang Database, and China Biology Medicine disc (CBM) from their inception through April 2025. Randomized controlled trials (RCTs) including adult patients (age ≥18 years) diagnosed with post-stroke aphasia will be eligible. The primary outcomes will be changes in overall language function (e.g., using the Western Aphasia Battery) and functional communication ability (e.g., using the Communicative Effectiveness Index). Secondary outcomes will include a dichotomized overall effective rate (based on predefined improvement thresholds reported in the primary studies), quality of life, and adverse events. Outcomes will be analyzed at two pre-specified time points: immediately post-treatment (within 4 weeks of the final session) to assess short-term efficacy, and at long-term follow-up (≥3 months post-treatment) to assess the durability of effects. The quality of included trials will be evaluated using the Cochrane risk bias measurement tool: Risk of Bias 2 (RoB 2). Meta-analysis will be performed using standard review software (e.g., RevMan). Advanced analyses, including meta-regression to explore sources of heterogeneity, will be conducted using the R statistical environment. If meta-analysis is inappropriate due to extreme heterogeneity, a narrative synthesis will be conducted.DiscussionThis study will provide a comprehensive systematic review and meta-analysis focused on RCTs evaluating acupuncture for post-stroke aphasia. Publishing this protocol ensures transparency and outlines the methodology rigorously to avoid duplication. The results aim to provide clinicians and researchers with consolidated evidence regarding the role of acupuncture in post-stroke aphasia management and may inform future clinical guidelines and research directions.